Enhancing player engagement through game balancing in digitally augmented physical games. Issue 103 (July 2017) - Altimira, David; Mueller, Florian 'Floyd'; Clarke, Jenny; Lee, Gun; Billinghurst, Mark; Bartneck, Christoph
Abstract: Game balancing can be used to compensate for differences in players' skills, in particular in games where players compete against each other. It can help providing the right level of challenge and hence enhance engagement. However, there is a lack of understanding of game balancing design and how different game adjustments affect player engagement. This understanding is important for the design of balanced physical games. In this paper we report on how altering the game equipment in a digitally augmented table tennis game, such as the table size and bat-head size statically and dynamically, can affect game balancing and player engagement. We found these adjustments enhanced player engagement compared to the no-adjustment condition. The understanding of how the adjustments impacted on player engagement helped us to derive a set of balancing strategies to facilitate engaging game experiences. We hope that this understanding can contribute to improve physical activity experiences and encourage people to get engaged in physical activity. Abstract : Highlights: We study the effects of game adjustments on game balancing and player engagement. We study how digital technology can be used as a resource for game balancing. Dynamic adjustments enhance player engagement more than static ones. Game adjustments can moderate the influence of a player on the other's performance. Game balancing design strategies are outlined.